Associating Psychological Factors With Workplace Satisfaction and Position Duration in a Sample of International School Teachers - Hollett, Ross C.; McMahon, Mark; Monson, Ronald (Frontiers in Psychology, 2021)
To be an effective teacher, a combination of specific professional skills and psychological attributes are required. With increasingly fluid employment conditions, particularly in the international context, recruiters and schools are under considerable pressure to quickly differentiate candidates and make successful placements, which involves more than just determining if a candidate holds an appropriate qualification. Therefore, the aim of this cross-sectional study was to measure theoretically and empirically valuable psychological attributes in an international sample of schoolteachers to determine the most valuable correlates of satisfaction and position duration. An international sample (N = 335) of elementary, middle and high school teachers completed an online survey to capture their workplace satisfaction, position duration and measure 15 psychological attributes using validated instruments. Linear associations were estimated using hierarchical regression with this analysis complemented and compared with follow-up non-linear neural network models. Using regression, lower agreeableness (less people-oriented) emerged as the strongest correlate of longer position duration throughout the cohort. In elementary school teachers, lower impulsivity and higher organizational commitment emerged as the strongest correlates of longer position duration. In high school teachers, better stress tolerance and higher organizational commitment emerged as the strongest correlates of longer position duration. Using neural networks to suggest predictive models, low levels of neuroticism and impulsivity were the strongest predictors of longer position duration in elementary school teachers. High stress tolerance also predicted high work satisfaction in elementary teachers, whereas it was lower impulsivity that most strongly predicted higher work satisfaction in high school teachers. Innovation tendencies, perhaps surprisingly, appeared as a consistent predictor of lower levels of workplace satisfaction across teaching levels. Honesty-humility also emerged as a predictor of shorter position duration, particularly for primary/elementary teachers scoring above the mean. Taken together the results suggest an interesting balancing act that needs to be struck between hiring people-oriented and innovative teachers who may be more effective and adaptable but also at greater risk of changing position, possibly due to an increased interest and ability to transition into new social environments.